First-principles study on structural, electronic and optical properties of perovskite solid solutions KB1−xMgxI3 (B = Ge, Sn) toward water splitting photocatalysis. Issue 42 (3rd August 2021) - Ri, Chol-Hyok; Kim, Yun-Sim; Jong, Un-Gi; Kye, Yun-Hyok; Ryang, Se-Hun; Yu, Chol-Jun
Abstract : We propose lead-free potassium iodide perovskite solid solutions KBI3 with B-site mixing between Ge/Sn and Mg as potential candidates for photocatalysts based on systematic first-principles calculations. Abstract : Perovskite materials have been recently attracting a great amount of attention as new potential photocatalysts for water splitting hydrogen evolution. Here, we propose lead-free potassium iodide perovskite solid solutions KBI3 with B-site mixing between Ge/Sn and Mg as potential candidates for photocatalysts based on systematic first-principles calculations. Our calculations demonstrate that these solid solutions, with proper Goldschmidt and octahedral factors for the perovskite structure, become stable by configurational entropy at finite temperature and follow Vegard's law in terms of lattice constant, bond length and elastic constants. We calculate their band gaps with different levels of theory with and without spin–orbit coupling, revealing that the hybrid HSE06 method yields band gaps increasing along the quadratic function of Mg content x . Moreover, we show that the solid solutions with 0.25 ≤ x ≤ 0.5 have appropriate band gaps between 1.5 and 2.2 eV, reasonable effective masses of charge carriers, and suitable photoabsorption coefficients for absorbing sunlight. Among the solid solutions, KB0.5 Mg0.5 I3 (B = Ge, Sn) is found to have the most promising band edge alignment with respect to the water redox potentials with different pH values, motivating experimentalists to synthesize them.